Pendidikan Moral Anak Usia Dini melalui Kisah Nabi Yunus dalam Surah Al-Anbiya' (21:87-88) dan Korelasinya dengan Teori Lawrence Kohlberg - Yanti, Yanti; Hayani, Aida (Jurnal I TIBAR, 2024)
This study examines early childhood moral education through the story of Prophet Yunus in Surah Al-Anbiya' (21:87-88) and its correlation with Lawrence Kohlberg's theory. The research method employed is library research, aimed at answering research questions through a critical literature review on how early childhood moral education through the story of Prophet Yunus in Surah Al-Anbiya' (21:87-88) correlates with Lawrence Kohlberg's theory. The results indicate the effectiveness of story-based learning in shaping the morals of young children, consistent with Piaget and Bandura's theories. Additionally, there is a correlation between the story of Prophet Yunus reflecting the stages of moral development described by Kohlberg, such as the importance of forming moral foundations early on, stages of moral development, development of moral awareness, and acceptance of Allah's decree. Thus, Islamic religious education in early childhood can help establish strong moral foundations and foster good moral awareness in accordance with moral learning and moral development theories.